Renaissance for low shrinking resins: All-in-one solution by bi-functional vinylcyclopropane-amides - Contreras, Paul Pineda; Kuttner, Christian; Fery, Andreas; Stahlschmidt, Ullrich; Jerome, Valerie; Freitag, Ruth; Agarwal, Seema (Chemical Communications, 2015)
A low volume shrinking vinylcyclopropane (VCP) monomer, showing both a high reactivity and a low viscosity, was obtained by applying a sterically hindered and isomeric spacer element, incorporating intermolecular amide hydrogen bonds. The resulting properties locate this VCP system in a pronounced range that so far no other efficient and radical polymerizable resin could enter.
CRIS-Team Scopus Importer:2023-03-20